2015
DOI: 10.1007/s11814-015-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Promoting role of sulfur groups in selective catalytic reduction of NO with NH3 over H2SO4 modified activated carbons

Abstract: To determine the role of sulfur groups formed on activated carbon (AC) in the selective catalytic reduction (SCR) of NO with NH 3 , coal-based AC was modified by H 2 SO 4 under various conditions and then treated in N 2 atmosphere at 400 o C. The resulting carbons were characterized by N 2 adsorption, elemental analysis, temperature programmed desorption and X-ray photoelectron spectroscopy, and tested for the SCR of NO with NH 3 in the temperature range of 30-250 o C. Results reveal that H 2 SO 4 modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The other two peaks at 169.63 eV (2p 3/2 ) and 170.73 eV (2p 1/2 ) belong to sulfates. 31,32 For fresh Na(0.45)-SAC (Figure 6a), all of these peaks were weak. After the reaction (Figure 6b), the peaks of S 8 increased strongly, but the peaks of sulfates changed little, indicating that S 8 was the main product after removal of COS and H 2 S over Na(0.45)-SAC.…”
Section: Removal Mechanism Over Modified Sacmentioning
confidence: 99%
“…The other two peaks at 169.63 eV (2p 3/2 ) and 170.73 eV (2p 1/2 ) belong to sulfates. 31,32 For fresh Na(0.45)-SAC (Figure 6a), all of these peaks were weak. After the reaction (Figure 6b), the peaks of S 8 increased strongly, but the peaks of sulfates changed little, indicating that S 8 was the main product after removal of COS and H 2 S over Na(0.45)-SAC.…”
Section: Removal Mechanism Over Modified Sacmentioning
confidence: 99%
“…Most modification methods can improve the BET specific surface area and total pore volume. However, some modification methods reduce the BET specific surface area and total pore volume, but the surface functional groups and some specific properties can be improved to some extent. , Therefore, the BET specific surface area and total pore volume cannot be simply used to evaluate the modification effect of CAC. Instead, the modification effect should be evaluated according to the specific application.…”
Section: Modification Of Cacmentioning
confidence: 99%
“…He et al 98 found that although the BET specific surface area and total pore volume of CAC modified with silane decreased, the humidity of cigarette smoke treated with silane-modified CAC was greater. Guo et al 99 studied the influence of H 2 SO 4 modification and subsequent pyrolysis treatment on the pore structure and surface chemistry of CAC. The results showed that H 2 SO 4 modification had little effect on the BET specific surface area and total pore volume but promoted the formation of sulfur and oxygen groups.…”
Section: Modification Of Cacmentioning
confidence: 99%
“…Activated carbon is used widely for the adsorption of noxious gases and heavy metals, as well as for wastewater treatment because of its large adsorption capacity, large surface area, and high porosity [16][17][18][19][20][21][22][23][24][25]. On the other hand, the price of commercial activated carbon produced from bituminous coal, coconut shell, wood, or peat is relatively high because of the costly raw materials and expensive activation process [26].…”
Section: Characterization Of the Charmentioning
confidence: 99%